2009
DOI: 10.1080/00218460902880313
|View full text |Cite
|
Sign up to set email alerts
|

Single-Lap Joints of Similar and Dissimilar Adherends Bonded with an Acrylic Adhesive

Abstract: In this study, the tensile strength of single-lap joints (SLJs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(52 citation statements)
references
References 34 publications
1
51
0
Order By: Relevance
“…adhesives [8,25], and this is particularly critical when considering stiff adherends, due to the practically absence of differential deformation effects in these components along the overlap [23,26]. In contrast, triangular CZM are efficient for brittle materials that do not plasticize by a significant amount after yielding [27], and also for the intralaminar fracture of composite adherends in bonded structures, due to their intrinsic brittleness [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…adhesives [8,25], and this is particularly critical when considering stiff adherends, due to the practically absence of differential deformation effects in these components along the overlap [23,26]. In contrast, triangular CZM are efficient for brittle materials that do not plasticize by a significant amount after yielding [27], and also for the intralaminar fracture of composite adherends in bonded structures, due to their intrinsic brittleness [28].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the effect of the CZM law shape on the strength predictions significantly varies depending on the structure geometry and post-elastic behaviour of the materials. These issues became evident in the experimental and FE study of Pinto et al [23], whose objective was the strength comparison of single-lap joints with similar and dissimilar adherends and values of adherend thickness, tP, bonded with the adhesive 3M DP-8005 s . The accurate shape of the CZM law was considered fundamental for the strength prediction and P-d response of the structure when using stiff adherends.…”
Section: Introductionmentioning
confidence: 99%
“…More uniform stress fields, capability of fluid sealing, high fatigue resistance and the possibility to join different materials are other advantages of this technology. However, stress concentrations exist in bonded joints along the bond length owing to the gradual transfer of load between adherends and also the adherends rotation in the presence of asymmetric loads [2]. A large amount of works addresses the critical factors affecting the integrity of adhesive joints, such as the parent structure thickness, adhesive thickness, bonding length and geometric modifications that reduce stress concentrations [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…By comparing with Fig. 10 (tS ¼ 2 mm), an improvement of strength by increasing tS was found (5.5% for configuration 1), which can be explained by the increasing bending stiffness of the adherends and corresponding reduction of the peel effects [10]. In fact, the adherends opposed curvature resulting from the asymmetry of loading in single-lap joints results on a separation of the adherends at the overlap edges and compression in-between.…”
Section: Resultsmentioning
confidence: 97%
“…Finite Element simulations showed that shear peak stresses in the adhesive bond can be reduced by 20%. Pinto et al [10] showed by a Finite Element (FE) stress and failure analysis that increasing the stiffness of the adherends materials in single-lap joints leads to a reduction of the joint bending, which diminished stresses at the overlap edges and, consequently, increased the strength of the joints.…”
Section: Introductionmentioning
confidence: 99%